2021
DOI: 10.3390/w13101396
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Flow Behavior in a Rectangular Channel with Submerged Weirs

Abstract: In this contribution, different 3D numerical approaches are applied in order to simulate the behaviour of turbulent flow through a rectangular channel with broad-crested weirs. In addition, water flow velocities, using Acoustic Doppler Velocimetry (ADV) instrumentation, were recorded. Two turbulence quantities are estimated using the laboratory records and were compared with those computed with the Large Eddy Simulation (LES) and Reynolds Averaged Navier–Stokes (RANS) models. Additionally, a quadrant analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Turbulence flow behavior through a rectangular confluence channel was also investigated by Herrera-Granados (2021) [28] and laboratory records were compared with the simulation results of LES and RANS models. The model output was in good agreement with time-averaged factors but was not sufficient for the proper estimation of the turbulence quantities.…”
Section: Schindfessel Et Al (2017)mentioning
confidence: 99%
“…Turbulence flow behavior through a rectangular confluence channel was also investigated by Herrera-Granados (2021) [28] and laboratory records were compared with the simulation results of LES and RANS models. The model output was in good agreement with time-averaged factors but was not sufficient for the proper estimation of the turbulence quantities.…”
Section: Schindfessel Et Al (2017)mentioning
confidence: 99%
“…The results showed that the output of the models are in good agreement with time-average factors, but is not sufficient for the proper estimation of the turbulence quantities. [29] LES was discussed in [33] where an open-channel confluence flow was studied using LES to utilize a frictionless rigid-lid to treat the free-surface. Rigid lid approach in the simulation of an asymmetric confluence was used to analyze the limitation of the free-surface treatment.…”
Section: Tang Et Al (2018)mentioning
confidence: 99%